2017
DOI: 10.19175/recom.v7i0.1934
|View full text |Cite
|
Sign up to set email alerts
|

O v�nculo com o profissional de sa�de no tratamento de tuberculose: percep��o dos usu�rios

Abstract: RESUMO ABSTRACTObjective: to analyze the relationship with health professionals working in the treatment of tuberculosis in centralized and decentralized health services, from the patients' perspective. Method: evaluative study, in which we interviewed 89 patients using the Primary Care Assessment Tool, validated in Brazil and adapted for assistance in TB. The data satisfied our assumptions of independence, homoscedasticity and normality and were subjected to variance analysis; the others, to the Kruskal-Walli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 12 publications
(24 reference statements)
0
6
0
7
Order By: Relevance
“…Os usuários apoiados conseguem participar ativamente da superação dos seus problemas, estabelecer decisões e as assumirem no seu viver. O vínculo, portanto, constitui um dos principais elementos estruturantes na atenção e no controle da TB, uma vez que ele permeia a responsabilização, a integralidade, a humanização, entre outros (Furlan et al,2017).…”
Section: Fatores Relacionados à Adesão Ao Tratamento E O Vínculo Usuário / Profissionalunclassified
“…Os usuários apoiados conseguem participar ativamente da superação dos seus problemas, estabelecer decisões e as assumirem no seu viver. O vínculo, portanto, constitui um dos principais elementos estruturantes na atenção e no controle da TB, uma vez que ele permeia a responsabilização, a integralidade, a humanização, entre outros (Furlan et al,2017).…”
Section: Fatores Relacionados à Adesão Ao Tratamento E O Vínculo Usuário / Profissionalunclassified
“…The link has a close relationship with the care practices, since both promote harmony, exchange of affections and coexistence potentially reconstructive of autonomies. 19 It is revealed that, in order to evaluate the performance of the PHC services in the detection of TB cases, E5 and E6 had the participation of doctors, nurses and nursing technicians. It is specified that study E6 added the evaluation of the capacity of the services for attention to respiratory symptomatics (RS) and community health agents (PHC).…”
Section: Cross-sectional and Quantitativementioning
confidence: 99%
“…A linha de cuidado para os pacientes com TB, preconizada pelo MS, é pautada nas diretrizes de acolhimento, no âmbito da Atenção Primária à Saúde (APS), com assistência continuada e de qualidade, além de prever a instauração de vínculo profissional-paciente, com a finalidade de facilitar o acesso ao serviço e a adesão ao tratamento. Assim, o vínculo é tido como um forte elemento de fortalecimento, relatado pelos doentes, e que contribui para a adesão ao tratamento, conforme os achados deste estudo e de outros (Souza et al, 2010;Galavote et al, 2015;Andrade et al, 2016;Furlan, Santos Junior, Marcon, 2017;).…”
Section: I S C U S S ã O | 158unclassified
“…Furlan, Santos Junior, Marcon (2017) 2010, Sá et al (2012), Chikovore et al (2014) e Barua, Van Driel, Jansen (2018).…”
Section: I S C U S S ã O | 158mentioning
confidence: 99%
See 1 more Smart Citation